2001
DOI: 10.1063/1.1400780
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of He4 droplets

Abstract: Optimized variational calculations have been carried out for clusters of 4 He between Nϭ20 and Nϭ1000 atoms. For small cluster sizes with less or equal to 112 particles, where comparisons with existing diffusion Monte Carlo results are possible, we find good agreement for the ground state energies and densities. Using a somewhat simpler approximation, we also calculate the bound state energies of 3 He atoms attached to these clusters. We then calculate excitations and the dynamic structure function. The comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…A more general method, that calculates the normal modes using time dependent, density functional theory is under development [96] and will give the entire phonon spectrum, but with the limitations of present density functionals which are unreliable for external potentials with very attractive interactions. Krotscheck and coworkers have used variational Monte-Carlo methods [97] and quantum many-body methods known as HNC/EC [98], Random Phase Approximation and Correlated Basis Function methods [11] to study the lowest excitations of each angular momentum in pure and doped droplets.…”
Section: Helium Droplet Excitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more general method, that calculates the normal modes using time dependent, density functional theory is under development [96] and will give the entire phonon spectrum, but with the limitations of present density functionals which are unreliable for external potentials with very attractive interactions. Krotscheck and coworkers have used variational Monte-Carlo methods [97] and quantum many-body methods known as HNC/EC [98], Random Phase Approximation and Correlated Basis Function methods [11] to study the lowest excitations of each angular momentum in pure and doped droplets.…”
Section: Helium Droplet Excitationsmentioning
confidence: 99%
“…Moreover, the quantum nature and in particular the superfluid properties of the droplets allow one to investigate these quantum properties in a size-limited aggregate on the nanometer scale. Today the field of helium droplets is well established and several review articles have appeared during the last decade highlighting a variety of experimental as well as theoretical aspects [2,3,4,5,6,7,8,9,10,11,12,13,14]. In this paper, we will not attempt a comprehensive overview of the entire field because many experimental as well as theoretical approaches have already been reviewed, summarized and pointed out.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially these ionic snowballs can also be used to probe the properties of helium nanodroplets. These droplets are created by condensation of the expanding helium gas and reach a limiting temperature of about 0.37 K [6,7], clearly below the superfluid transition temperature in liquid 4 He, T λ = 2.17 K. Early Quantum Monte Carlo (QMC) calculations indicated that a very small droplet containing less than 100 atoms already displays features pertaining to the superfluid state of bulk liquid helium [8][9][10][11]. This was later confirmed in a cornerstone experiment by Toennies and co-workers on mixed 3 He- 4 He droplets doped with carbonyl sulfide (OCS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [13,14], but not in Refs. [9,10,15], the effect of this approximation on the DMC results has been discussed in Ref.…”
mentioning
confidence: 96%